Mortality from Parkinson's disease in China: Findings from a five-year follow up study in Shanghai. (20th May 2015) - Wang, Gang; Li, Xin-Jian; Hu, Yi-Song; Cheng, Qi; Wang, Chun-Fang; Xiao, Qin; Liu, Jun; Ma, Jian-Fang; Zhou, Hai-Yan; Pan, Jing; Tan, Yu-Yan; Wang, Ying; et al.
Abstract Introduction: The mortality of Parkinson's disease (PD) and its associated risk factors among clinically definite PD patients in China has been rarely investigated. Our study aimed to identify the mortality rates and predictors of death in PD patients in China. Methods: 157 consecutive, clinically definite PD patients from the urban area of Shanghai were recruited from a central hospital based movement disorder clinic in 2006. All patients were regularly followed up at the clinic until December 31, 2011, or death. Mortality and associations with baseline demographics, health and medical factors were then determined within the cohort. Results: After 5 years, 11(7%) patients had died. The standardised mortality ratio was 0.62 (95% CI 0.32 to 1.07, P=0.104). The main causes of death were pneumonia (54.5%, 6/11) and digestive disorders (18.2%, 2/11), respectively. Age at onset, independent living, the mini mental state examination score, the Parkinson's disease sleep scale score and the Epworth sleepiness scale score at baseline were statistically significantly different between the survival group and the deceased group (P<0.05). Across all participants, risk factors for death included low mini mental state examination score, and high Epworth sleepiness scale score according to a binary variable logistic regression analysis. Conclusions: This study confirms the similar survival of patients with PD to the control population up to a follow-up of 5 years. Interventions tailored to potential risk factors associated with death may offer further benefits.